Examining Communication and Patient Recall in a Family Medicine Residency - Ebberwein, Christopher; Woods, Nikki Keene; Terrell, Holly Allen; Boyce, Mary; Reyes, Jared; Chesser, Amy (Kansas Journal of Medicine, 2013)
Background. Understanding key aspects of effective physician-patient communication could benefit residency education and improve patient comprehension of health information. Discrepancies between what physicians say and what patients understand can reduce quality of care (e.g., patient adherence and satisfaction), making it imperative to know when gaps in patient understanding exist. The objective of this study was to identify residents’ efforts to assess patient understanding and the degree to which patients recalled information and instructions provided in the medical encounter. Methods. Residents and patients were observed in routine medical encounters in a Midwestern family medicine residency center. Patients were surveyed immediately following the encounter for recall of information and recommendations from the encounter, satisfaction with physician communication, and health literacy. Results. A total of 21 physician-patient encounters were observed. An inverse relationship was noted (Spearman’s rho = -0.43, N = 21, p = 0.05) between number of topics discussed during the encounter and the percentage of information recalled. Conclusions. Patient recall was related inversely to the number of topics covered by resident physicians. These results challenge physicians and medical educators to study and employ further those elements of physician-patient communication that enhance patient recall and understanding.